Bacterial immunotherapy: is it a weapon in our arsenal in the fight against cancer? - Sharma, Shubhra; Sharma, Himani; Gogoi, Himanshu (Frontiers in Immunology, 2023)
Advances in understanding the genetic basis of cancer have driven alternative treatment approaches. Recent findings have demonstrated the potential of bacteria and it's components to serve as robust theranostic agents for cancer eradication. Compared to traditional cancer therapies like surgery, chemotherapy, radiotherapy, bacteria mediated tumor therapy has exhibited superior cancer suppressing property which is attributed a lot to it's tumor proliferating and accumulating characteristics. Genetically modified bacteria has reduced inherent toxicity and enhanced specificity towards tumor microenvironment. This anti-tumor activityefficacy of bacteria is attributed to it's toxins and other active components from the cell membrane, cell wall and spores. Furthermore, bacterial genes can be regulated to express and deliver cytokines, antibodies and cancer therapeutics. Although there is less clinical data available, the pre-clinical research clearly indicatesstates the feasibility and potential of bacteria-mediated cancer therapy.